2016
DOI: 10.1016/j.dld.2015.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Faecal microbiota transplantation in recurrent Clostridium difficile infection: Recommendations from the French Group of Faecal microbiota Transplantation

Abstract: Faecal microbiota transplantation is effective for treating recurrent forms of Clostridium difficile infection and its use in this indication is recommended in the most recent European and North American guidelines. In this context, faecal microbiota transplantation is beginning to be performed in France in clinical practice, while the rules governing this procedure have been defined in France only for clinical trials. To unify, secure, and evaluate practice in this field in France, the French Group of Faecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 13 publications
1
47
0
12
Order By: Relevance
“…The above recommendation is supported by excellent safety data from several RCTs,1 2 14 15 and is also reported in the French National Guidelines of FMT for rCDI 22…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…The above recommendation is supported by excellent safety data from several RCTs,1 2 14 15 and is also reported in the French National Guidelines of FMT for rCDI 22…”
Section: Resultssupporting
confidence: 57%
“…In addition, further exclusion criteria, especially those related to the presence of GI disorders, or drugs which may impair microbiota, were considered, based on available evidence. Indeed, the use of these or similar exclusion criteria assured, as shown in several RCTs, large case series and systematic review,1–3 5 7 14–16 36 the occurrence of no or few adverse events related to the infusion of donors' material, as also stated in the French National Guidelines of FMT for the treatment of rCDI 22…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Le donneur apparaît alors comme une sorte de bioréacteur produisant un matériel d'intérêt thérapeutique [26]. Pour unifier et sécuriser la transplantation de microbiote fécal, qui entre déjà dans la pratique pour les infections récurrentes à Clostridium difficile, le Groupe français de transplantation fécale (GFTF) vient de publier des recommandations concernant ses indications, la sélection des donneurs, la préparation et l'administration du transplant, ainsi que sa traçabilité [28]. La même question se pose pour le don de matières fécales dans un but de recherche.…”
Section: Un Organe Transplantableunclassified
“…Importantly, FMT is a non-standardized procedure, and the long-term consequences of altering a patient's gut microbiota are unknown. Several national guidelines have, therefore, been developed to standardize FMT, including donor screening and selection [207][208][209] . Results from a preliminary study among patients with relapsing CDI revealed that administration of FMT using frozen encapsulated inoculum from unrelated donors also resulted in a good outcome 210 .…”
Section: Bacteriotherapy and Faecal Transplantationmentioning
confidence: 99%